LAJU PERTUMBUHAN DAPHNIA MAGNA DENGAN PEMBERIAN PUPUK ORGANIK BERBEDA - Laili, Nur; Zulfadhli, Zulfadhli; Fadhillah, Radhi; Mahendra, Mahendra (JURNAL AKUAKULTURA, 2022)
This study aims to determine the growth rate of Daphnia magna with different organic fertilizers. This research is an experimental study using CRD (completely randomized design) with 3 treatments (p) and 3 replications (u). The organic fertilizer treatments applied to daphnia culture media were: P0 = Control, P1 = Cow dung, P2 = Swallow Manure, and P3 = Chicken Manure. Parameters measured included specific growth rate, and population density of daphnia. Data were analyzed statistically (Anova). The results showed that the application of organic cow dung, swallow and chicken manure had a significant effect on the specific growth rate and population density of daphnia (P<0.05). The best treatment was on P2 (swallow droppings) with a specific growth rate of 19.9%/day and a population density of 1635 ind/L